CREATIVE APPROACHES TO DEVELOPING MANAGEMENT AND ENTREPRENEURSHIP SKILLS IN ENTREPRENEURS - Abdumo‘minova Maftuna Abdulhamid qizi; Ismoilova Shahnoza Abdumalik qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation: This article presents information about the necessary conditions created for the development of management and entrepreneurship skills in entrepreneurs, as well as foreign experience and innovative methods to stimulate interest in entrepreneurship.